A comprehensive study on physico-mechanical properties of non-metallic fibre reinforced SCC blended with metakaolin and alcofine. (1st December 2022) - Vivek, S S; Karthikeyan, B; Selvaraj, Senthil Kumaran; Pradeep Kumar, M; Chadha, Utkarsh; Das, Sreethul; Ranjani, G; Rajasakthivel, R; Tamilvendhan, K; Adane, Tezeta Moges
Abstract: This study presents a detailed experimental investigation on the effects incorporating non-metallic fibers in hybrid form in self-compacting concrete (SCC). In this regard SCC was prepared with Alccofine and Metakaolin as partial replacement for cement in 15% and 20% respectively along with the hybrid fibre combinations namely abaca fibres (0.25%, 0.5% & 0.75%), polypropylene fibres (0.5%, 1%, 1.5% & 2%) and glass fibres (0.5%, 1%, 1.5%, & 2%). The fresh properties of SCC with and without hybrid fibre combinations were assessed through the standard tests such as slump flow, J ring and V-funnel tests. The conventional mechanical tests such as compressive strength test, split tensile strength test and flexural strength test were performed at 7 and 28 days. The experimental results reveal that the fresh properties of SCC were highly influenced by alccofine and Metakaolin adopted in this research. Furthermore, that the hybrid combination of abaca with polypropylene and glass fibres improved the mechanical properties of SCC and in particular the mix with 1% glass fibre and 0.25% Abaca fibre had shown better flexural and tensile strength behaviour. Microstructure analyses were also done to confirm the improvement in mechanical properties. The Scanning Electron Microscope images of the mix with 1% glass fibre and 0.25% abaca fibre showed less voids presence and presence of more hydrated components conveying that the usage of hybrid fibres had restricted the propagation of cracks there by reducing the percentage of voids and the use of metakaolin and alcofine helping in forming hydrated components at earlier stage leading to better strength.